Analysis Of Factors That Influence Generation Z'S Intention To Switch To Using Cloud Storage Services With The Push-Pull-Mooring Framework - Tarigan, Arihta; Putra, I Gede Wisnu Satria Chandra; Nattassha, Ruth; Eldelin, Eldelin; Karina, Fiona (Jambura Economic Education Journal, 2026)
This study focuses on analyzing Gen-Z's habits in using cloud storage services using the push-pull-mooring framework. Currently, Generation Z has widely used cloud storage services to facilitate their daily activities, supported by the many service providers offering cloud storage services with various types of services and different features. Various factors that encourage, attract, and moor (Push-Pull-Mooring) Generation Z to use cloud storage services in the form of SaaS (Software as a Service) services such as simplicity, usefulness, security, privacy, habit, and switching cost. The study was conducted using a quantitative method using purposive sampling. Data were processed using SPSS version 26. The results of the study based on data from 104 respondents are that habit has a partial effect on switching intention. Meanwhile, simplicity, usefulness, security, privacy, habit, and switching cost have a significant effect simultaneously on switching intention.